(untitled) (Research, Society and Development, 2022)
The tomato, widely distributed around the world, is one of the main oleraceae species, being considered the second vegetable in volume of production and consumption. Thus, research on crop conduction systems and post-harvest studies becomes essential. In this sense, the objective was to analyze the quality of tomato produced in a protected environment in the region of Alta Paulista/SP. The experiment was carried out at the Regional Unit for Research and Development of Adamantine of APTA Regional, in Adamantina/SP, year 2021. "Italiano" tomato seed of determined growth was used. The fruits were divided into “commercial (table)” or “disposal (agro-industrial processing)”. Fresh mass (g), fruit height and mean diameter (mm), soluble solids (oBrix) and fruit utilization (%) were evaluated. A completely randomized design was used with two treatments and 8 replications. The data were submitted to analysis of variance for the F test and the means were compared by the Tukey test at a 5% significance level. A significant difference was observed for all variables, with the exception of soluble solids. Fresh mass, height and fruit utilization were the items with the greatest quantitative variations, respectively. The fruits classified as “discard” showed a percentage of utilization of 85.25±5.82. This result showed that the production classified as "discard" can be sold for consumption in natura at a lower price compared to the fruits selected for the table. It can also be used for family consumption (as a sauce). It was concluded that, under the conditions in which the work was carried out, the “Italiano” tomato evaluated in a protected environment in Alta Paulista/SP proved to be suitable for consumption for the table and agro-industrial processing, thus being recommended for commercial cultivation.